2021
DOI: 10.3390/genes12040550
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-2 and Its Transcript Variants Correlate with Clinical Outcome in Bladder Cancer

Abstract: Urothelial bladder cancer ranks among the 10 most frequently diagnosed cancers worldwide. In our previous study, the transmembrane protein neuropilin-2 (NRP2) emerged as a predictive marker in patients with bladder cancer. NRP2 consists of several splice variants; the most abundant of these, NRP2a and NRP2b, are reported to have different biological functions in lung cancer progression. For other cancer types, there are no published data on the role of these transcript variants in cancer progression and the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Although NRP2 is frequently overexpressed in tumors and associated with poor clinical outcomes, the role of the NRP2 isoforms and their impact on macrophages in the TME remains undefined ( 8 , 34 39 ). We examined specimens from 99 breast cancer patients where both primary tumors and metastases underwent ecRNA-seq.…”
Section: Resultsmentioning
confidence: 99%
“…Although NRP2 is frequently overexpressed in tumors and associated with poor clinical outcomes, the role of the NRP2 isoforms and their impact on macrophages in the TME remains undefined ( 8 , 34 39 ). We examined specimens from 99 breast cancer patients where both primary tumors and metastases underwent ecRNA-seq.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning KDR, there are not many published data KDR in PC. Just A. Fraga et al demonstrated that KDR−604 T > C was correlated with protein level, accounting for a potential geneenvironment effect in the activation of hypoxia-driven pathways in PC (Förster et al, 2021). In colorectal cancer, for example, a significant association was found between KDR expression, disease stage and lymph status (Fraga et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been identified as an important prognostic marker for worse clinical outcome especially in patients with high PC risk ( Borkowetz et al, 2020 ). There is scarce data according to PC but in other tumors such as bladder cancer, high messenger RNA expression of NRP2, NRP1, PDGFC , and PDGFD are associated with a more aggressive disease (i.e., a high T stage, positive lymph node status and reduced survival) ( Förster et al, 2021 ). Present data reports similarities as previously described in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of P4HB may promote the progression of malignant tumors, including gastric cancer, renal clear cell carcinoma, and bladder cancer, and the expression of P4HB mRNA possesses a notably high level in advanced pathological T-stage (24). PDGFD messenger RNA expression levels correlate with disease severity (i.e., high T-stage, positive lymph node status, and reduced survival) (25). Rac3 is a GTPase that belongs to the Rho family and is regulated by C3 botulinum toxin.…”
Section: Discussionmentioning
confidence: 99%